(untitled) (Connecticut, 1986)
The American Presidents is a collection of articles that analyze and evaluate the presidential careers of the men who have occupied the office since its inception in 1789. In this volume, the leading presidential historians in the United States offer insights into what makes a president great, mediocre, or--in the case of most of them--something in between. The contributors to The American Presidents were not asked to write straightforward biographies of the presidents; other sources are available for that. Rather, they were asked to evaluate their subjects. No strict patterns were imposed by the editor; each author approached his or her subject in the way that best illustrated the strengths and weaknesses of the president under consideration.....
Keywords: Presidents,Presidents,United States,Các tổng thống Hoa Kỳ,Các tổng thống Hoa Kỳ; History,Biography, Politics and government.,Lịch sử,Tiểu sử; United States,United States